The TAB book of arduino projects: 36 things to make with shields and protoshields - Monk, Simon (McGraw-Hill's AccessEngineering, 2015)
In this easy-to-follow book, electronics guru Simon Monk show you how to create a wide variety of fun and functional gadgets with the Arduino Uno and Leonardo boards. Filled with step-by-step instructions and detailed illustrations, The TAB Book of Arduino Projects: 36 Things to Make with Shields and Proto Shields provides a cost estimate, difficulty level, and list of required components for each project. You'll learn how to design custom circuits with Proto Shields and solder parts to the prototyping area to build professional-quality devices. Catapult your Arduino skills to the next level with this hands-on guide.